IMPACT OF HEALTH EDUCATION INTERVENTION ON KNOWLEDGE OF CERVICAL CANCER PREVENTION AMONG WOMEN IN BAHOROK’S VILLAGE, NORTH SUMATRA INDONESIA - Rostime Hermayerni Simanullang (Belitung Nursing Journal, 2018)
Background: Cervical cancer is the second cancer disease that attacks women in the world, and it ranked the first in developing countries. It is expected that woman’s knowledge about cervical cancer will prevent the incidence among them. Objective: To examine the effect of health education on the knowledge level of women about cervical cancer prevention. Methods: This was a pre-experimental study with one group pretest posttest at Bahorok’s Village, North Sumatra, Indonesia on April to May 2016. There were 36 samples selected using purposive sampling. Paired t-test was used for data analysis. Results: There was a significant difference in the mean value of women knowledge levels (p=0.004), with the increase of the mean of knowledge before intervention (mean= 1.0) and knowledge after the intervention (mean= 2.14). Conclusion: There was a significant effect of health education in increasing the level of women knowledge about prevention of cervical cancer. It is suggested that that health education should be done routinely to increase women knowledge in order to prevent cervical cancer.